Key problems of telecom operators' NFV future network management system evolution - Qiu YUE; Ziyu XIAO; Lihua WU; Lei SHEN (Dianxin kexue)
Network function virtualization (NFV) is the core technology and architecture of telecom-level business to cloud,which is the inevitable trend of future network evolution.NFV brings new capabilities to the communications network,at the same time,it requires new management and orchestration (MANO) capabilities for existing equipment operations,management,maintenance and configuration models.First of all,the network management system architecture and future evolution planning of the physical network element were summarized,and by the coming of NFV technology,the changes of the existing network equipment management method and the new network management architecture and function were concluded.The coordination of NFV MANO and operation support system (OSS),NFV MANO and other peripheral network was deeply researched.Finally,from the perspective of telecom operators,the deployment and evolution strategy of NFV MANO based on decoupling level was suggested.